HUBUNGAN PERSEPSI TERHADAP IKLIM KELAS DENGAN MOTIVASI BELAJAR FISIKA SISWA SMA KELAS XI IPA SE KECAMATAN SIMPANG KANAN ROKAN HILIR - Kiswanto, Alex Kiswanto; Irianti, Mitri Irianti; sudrajat, Hendar sudrajat (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The purpose of this research is to know the correlation between perception of classroom climate and students learning motivation physics. This research is correlational.  The population in this study were students of class XI IPA Simpang Kanan sub-distric, sample in this study is one class from each school are Class XI IPA with a total of 115 people. and the sample in this study is one class from each school are Class XI IPA with a total sample of 43 people, The data collection instrument used is kuisioner classroom climate and and students learning motivation physics. The result of this research showed that there is a significant positive correlation between perception of classroom climate and students motivation to learn physic subject. Data analysis technique used is the Pearson product moment correlation test . Data were analyzed by descriptive and inferential. Based on the results of the analysis showed that there is a positive and significant correlation between perceptions of classroom climate with motivation to learn physics students, regression equation was Ῡ = 39.077 + 0.353 x, coefficient  of  correlation was 0,505 and Fcount > Ftable (14,001 > 3,99). Contribution perception of classroom climate and students motivation to learn physic subject was 22,5%.  The conclusion indicate that the perception of classroom climate relate to students motivation to learn physic in SMA class XI IPA simpang kanan sub-district . Keywords : Motivation To Learn, Classroom Climate, Perception